Kinematic Analysis of a KUKA YouBot - Τσόγιας, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Μηχανολογικών Κατασκευών και Αυτομάτου Ελέγχου. Εργαστήριο Αυτομάτου Ελέγχου και Ρυθμίσεως Μηχανών και Εγκαταστάσεων, 2016)
The increasing number of robot manipulators that are needed to complete a task, has made the creation of detailed control schemes a vital need. However, as the attention is placed primarily in the efficiency and stability of these schemes, it is therefore shifted from the creation of correct and detailed kinematics models. Such models constitute the basis of any control scheme as they provide basic knowledge about the properties of the system. The KUKA youBot manipulator is a manipulator mounted on a mobile platform developed for research and educational purposes. The five (low)-DOF manipulator is an interesting case study because its kinematics -especially its inverse kinematics problem- is actually complicated. In addition, the omnidirectional platform the manipulator is mounted on, is an interesting case itself too whether as omnidirectional or even if it was considered non-holonomic. The goal of this thesis is to develop a kinematic model for the KUKA youBot starting separately from its parts and afterwards for the system as a whole. Meanwhile, the properties of the system are explored with the help of various algebraic, geometric and linear algebra tools. In the first part of the thesis, the kinematics of the manipulator is detailed including forward, inverse kinematics, criterions that determine the existence, the correctness and the number of the inverse kinematics problem and singularity analysis with the Singular value Decomposition (SVD). The second part of the thesis includes the analysis of the platform in two scenarios: the omnidirectional case and the non-holonomic case. Last but not least, the same steps are followed for the composite system followed by an analysis of how close can the values of the joint go to ”dangerous” configurations (i.e. representational and internal singularities).